Table of Content - -, (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. The Role of Training Courses in Improving the Professional Performance of Principals in Private Schools in Bethlehem Governorate from their point of viewResearcher/ Grace Nasri Hazboun2. Education on Virtue in Islamic Educational Thought and Contemporary Western Philosophies - A Comparative Study.Dr.  HAILAH FAISAL H ALOQAYLI.3. Psychological counseling skills among female counselors in the secondary stage in the locality of KhartoumDr. Ghada El ameen Ahmed4. Reflective Thinking and its Relationship to Decision-Making Among Teachers of Gifted Students  in Makkah Al-MukarramahResearcher / Mada Khaled Al-Lahyani5. The Level of Mental Health among Omani Students with Learning Disabilities during Coronavirus Pandemic from their Parents' PerspectiveMs. Maryam H. Al-Hinai, Dr. Suhail M. Al-Zoubi, Dr. Zubaida S. Shebani6. Optimism and pessimism mediate the association between parental coronavirus anxiety  and depression among healthcare professionalsDr. Zainab Shalal Al-Anzi7. Challenges faced by female graduate students working in the private sectorMs. Raya Abdullah Al-Hammad, Ms.Fatima Jaber Al-Shehri, Ms.Ohood Saud Al-Shammari, Prof. Dr. Awatif Ibrahim Al-Saqri
Keywords: Journal of Educational and Psychological Sciences